Cultural Diversity in Pakistan: National vs Provincial - Shah, Syed Afzal Moshadi; Amjad, Shehla (Richtmann Publishing, 2011)
The purpose of the research was to investigate the cultural dimensions of the four provinces of Pakistan i.e. KhyberPakhtunkhwa, Punjab, Sindh, Balochistan of Pakistan and their comparison with national culture. The research capitalizes upon themethodology devised by Hofstede et. al (2008) in order to investigate the cultural dimensions. A total 557 questionnaires were used inorder to reach the final analysis by using descriptive statistics and test of significance. Research findings show an existence of a culturaldiversity among different provinces of Pakistan, where Khyber Pakhtunkhwa (KPK) possessing the most distinctive culture. Besideprovincial disparity with national culture on one to one basis, it does not affect the results on aggregate basis. Hence the national cultureremains a true representation of the country. The nature of subcultures within provinces and the level of their impact was the majorlimitation of the research. The research would benefit businesses in Pakistan at large both local and Multi-national organizations.VSM-08 is the latest version of all the methodologies devised by Hofstede. No study has yet been conducted in Pakistan to identifycultural dimensions on province level using the parameters defined in this model. Future research on different management and marketingaspects in Pakistani culture can be conducted in the light of this research.